Flow morphometry to assess the red blood cell storage lesion - Sierra Fajardo, Diego Andrés; Janetzko, Karin; Klüter, Harald; Bieback, Karen (Cytometry, 2017)
We present a novel automated system for morphology analysis of red blood cells (RBC) under flow. RBC concentrates collected by blood banks for transfusions are stored for periods of up to several weeks, during which time a number of changes occur, collectively termed the storage lesion. Typically the extent of hemolysis is the defining criterion to determine the acceptability of the RBCs for transfusions. Morphological changes are related with biochemical alteration during the storage of RBCs. The typical blood smear procedure for determining such changes is a labor-intensive and potentially biased manual process. The advantage of the flow morphometry system presented here is that it provides fully automated morphological classification of RBCs with large sample numbers in a short time. Our system uses a commercially available flow cell and flow conditions that prevent adhesion of RBCs, thus eliminating the need for blocking agents such as albumin that affect the distribution of cell shapes. Our morphometry results are validated by comparison with standard biochemical assays (hemolysis, ATP) for blood from 17 donors stored under blood bank conditions for 13 weeks. We show that the percentage of spherocytes present can be used to estimate the status of RBC concentrates. © 2017 International Society for Advancement of Cytometry